Hamstring and quadriceps strength ratio of crossfit athletes compared to basketball players and sedentary males - Aksoy, E. K.; Uzun, S. (International Journal of Applied Exercise Physiology, 2020)
CrossFit is a strenuous training program with growing popularity in recent years. It is important to determine the potential internal risk factors in the musculoskeletal system of the CrossFit athletes to minimize the already high injury risks of training.The objective of this study was to examine the imbalance in the strength of the knee extensor and flexor muscles of CrossFit athletes in relation to basketball players and sedentary males as control groups. Atotal of 51 voluntary individuals between 18 and 30 years old, consisting of 18 male basketball players, 15 male CrossFit athletes, and 18 sedentary male individuals participated in this study. The maximum concentric (60°/sec, 120°/sec, and 240°/sec)and eccentric (60°/sec, 120°/sec)knee extension and flexion torque parameters were measured by using isokinetic dynamometer, respectively. The functional H:Q ratio was calculated as the ratio of eccentric hamstring to the concentric quadriceps peak torques at each angular velocity. Concentric flexion andextension peak torque values were found to be significantly higher in basketball players and CrossFit athletes compared to sedentary males (p<0.05), except for flexion torques at 180°/s (p>0.05). Functional peak torque and average H:Q peak torque ratios of CrossFit athletes were significantly lower than the sedentary group at 1200/s (p<0.05). The knee extension and flexion strength of CrossFit athletes and basketball players found to be higher than sedentary males as expected because of their training background. Functional H:Q difference between CrossFit athletes and sedentary males showed CrossFit athletes` quadriceps muscles were stronger concentrically than their eccentric strength of hamstring muscles. These results indicate that strength training programs aimed at increasing hamstring strength, especially eccentrically may be beneficial for CrossFit athletes to minimize their injury risks.